PENGARUH KINERJA KEUANGAN TERHADAP PERTUMBUHAN EKONOMI DAERAH DENGAN ALOKASI BELANJA MODAL SEBAGAI VARIABEL INTERVENING (Studi pada Pemerintah Kabupaten/Kota D.I. Yogyakarta) - Kurni Adi Suwandi; Afrizal Tahar (InFestasi, 2015)
This study aims to to test empirically the influence of the financial performance of the local government which measured by the ratio of fiscal decentralization degrees, fiscal dependence, financial independence, the effectiveness of local revenue (PAD), and the degree of the contribution of BUMD to the ratio allocation capital expenditure. The population of this research is all local governments districts/city in D.I.Yogyakarta year 2003-2012. The result of this research shows thatthe ratio of degrees fiscal decentralization and fiscal dependence have a negative influence on the allocation of capital expenditure, the ratio of the effectiveness of local revenue (PAD) have a positive influence on the allocation of capital expenditure, and the ratio of the contribution of BUMD degrees does not affect the allocation of capital expenditure. The allocation of capital expenditure have a positive influence on the growth of regional economic. The allocation of capital expenditure cannot mediate the affect between the ratio of fiscal decentralization degrees, the effectiveness of local revenue (PAD), and the degree of the contribution of bumd on the growth of regional economic. But the allocation of capital expenditure can mediate the affect between fiscal dependence on the growth of regional economic.